2014
DOI: 10.1063/1.4891320
|View full text |Cite
|
Sign up to set email alerts
|

Particle-in-cell simulations of ion-acoustic waves with application to Saturn's magnetosphere

Abstract: Using a particle-in-cell simulation, the dispersion and growth rate of the ion-acoustic mode are investigated for a plasma containing two ion and two electron components. The electron velocities are modelled by a combination of two kappa distributions, as found in Saturn's magnetosphere. The ion components consist of adiabatic ions and an ultra-low density ion beam to drive a very weak instability, thereby ensuring observable waves. The ion-acoustic mode is explored for a range of parameter values such as κ, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…To validate our numerical analysis, we choose some typical parameters of Saturn's outer magnetosphere [58,59] as observed from the spacecraft. The observations showed that the Saturn's magnetosphere has three regions, the inner region [D (9-10)ρ s ], the middle region [D ∼ (7-14)ρ s ] and the outer region of magnetosphere [D ∼ (12-20)ρ s ] with ρ s (= 60270 km) represents radius of the Saturn.…”
Section: Resultsmentioning
confidence: 99%
“…To validate our numerical analysis, we choose some typical parameters of Saturn's outer magnetosphere [58,59] as observed from the spacecraft. The observations showed that the Saturn's magnetosphere has three regions, the inner region [D (9-10)ρ s ], the middle region [D ∼ (7-14)ρ s ] and the outer region of magnetosphere [D ∼ (12-20)ρ s ] with ρ s (= 60270 km) represents radius of the Saturn.…”
Section: Resultsmentioning
confidence: 99%
“…The soliton solution is found from the relation (12) where ϕ ξ is the first derivative of function ϕ with respect to ξ. n n e Below, results are given for calculations that were carried out for the following parameters of Saturn's magnetosphere (see [4,6,9]): n i0 = 10 cm -3 , T i = 100 K, T ec = 10 eV, T eh = 700 eV, , and κ c = κ h = 2.…”
Section: Soliton Solutionsmentioning
confidence: 99%
“…Also based on the data collected by the Voyager 1 spacecraft [5], it was shown that waves exist in the magnetospheric plasma of Saturn. Theoretical studies of ion acoustic waves in Saturn's magnetosphere were carried out in [6]. The dusty plasma in the vicinity of Saturn's satellite Enceladus was discovered during the Cassini mission [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In a kinetic simulation of IA wave propagation in two-electron temperature plasma, it has been found that the presence of a significant population of hot electron enhances the growth of IA wave. In contrast, the decrease in the effective electron temperature contributes to damping [34]. To observe the effect of hot electrons, an ion-acoustic wave is excited in the system, the details of which have already been described in section 2.…”
Section: Diagnosis By Ion-acoustic Wavementioning
confidence: 99%